Inuit materials, Frank Siebert Papers - Boas, Franz, 1858-1942; König, Herbert, 1911-1991; Speck, Frank G. (Frank Gouldsmith), 1881-1950 (1905)
The Inuit materials in the Siebert Papers are primarily composed of secondary sources located in Series IV and VII, labelled as "Eskimo."